Effect of Partial Doping with La Atoms on Some Superconducting and Electrotransport Characteristics of Y1-x LaxBa2Cu3Oy Polycrystals - Nikoghosyan, S. K.; Sargsyan, A. G.; Zargaryan, Y. G.; Aivazyan, A.; Hakopyan, A.
The effect of the location with different concentrations of La atoms (x = 0; 0.02; 0.028; 0.11) on some superconducting and electrotransport characteristics of Y1−xLaxBa2Cu3Oy polycrystalline compounds was studied by recording the temperature dependence ρ(T) curves of resistivity in the case of direct current in the range of temperatures (77K - 300K). The temperatures at the onset (Τcon) and offset (Tc0) of the transition, as well as the width of the transition - ΔΤc = Τcon-Tc0, were considered as the superconducting characteristics. The absolute values of ρ(300K) and ρ(100K) and their ratio a = ρ(300K)/ρ(100K) were considered as electric transport characteristics, as well as the temperature coefficient of resistivity dρ/dT, which was determined by ρ(T) in the range of linear dependence with the slope of the curve. From the comparison of these characteristics, it was concluded that there is a certain correlation between the superconducting and electrotransport properties of the studied compounds depending on the concentration x of the partial location of Y atoms with La.
Keywords: Physics